DEVELOPMENT OF HEAVY OIL HYDROCRACKING CATALYSTS - Redhwi, Halim H. (2020)
This paper present some results obtained from the research program being pursued at the Research Institute of King Fahd University of Petroleum and Minerals aimed at the development of suitable catalysts for hydrocracking of the vacuum gas oils from Arabian Light crude to obtain higher quality distillate products. The newly developed high-performance hydroprocessing catalysts are based on synthetic smectite clays and modified zeolites. Active metals have been incorporated into these novel supports to prepare several catalyst formulations for both stages of the conventional fixed-bed hydrocrackers. These novel catalysts have been characterized by sophisticated techniques and evaluated in different types of reactors (such as Pulse Microreactor, Batch Autoclave reactor, Fixed-bed Flow reactor etc.) using different feedstocks (e.g. model compounds and real VGO). Some of the formulations of developed catalysts have exhibited high performance in terms of hydrodesulfurization and cracking activities when compared to commercial catalysts under the same operating conditions. These catalysts are being further developed, comprehensively characterized, and thoroughly evaluated in order to come up with tailor-made catalyst formulations for hydrocracking of heavy petroleum fractions.